EVALUATION OF NURSES MENTAL HEALTH DURING THE COVID-19 PANDEMIC IN GOVERNMENT HOSPITAL IN PADANG CITY, INDONESIA - Rahmi Yosmar; Badriyya, Elsa (Malaysian Journal of Public Health Medicine, 2023)
The COVID-19 pandemic can impact on a person’s physical and mental health, increasing depression, anxiety, and stress. The nurse is one of the dominant professions in providing health services to patients. Therefore, researchers are interested in evaluating the nurses' mental health during the COVID-19 Pandemic in the government hospital in Padang City, Indonesia. This study aims to determine the nurses' mental health level and the factors influencing the condition. The research design used was non-experimental research with a comparative descriptive. The sample was chosen by consecutive sampling. The data was obtained from the demographic information questionnaire and the DASS-42 questionnaire from 108 nurses in the government hospital in Padang City. A total of 6.48%, 15.74%, and 8.3% of nurses experienced depression, anxiety, and stress categorized as mild to very severe based on this study. There was an association between the depression level of the nurse with gender, history of illness, and age, anxiety level with a history of illness, and the stress level of the nurse with gender and history of illness (p-value < 0.05). It can be concluded that most nurses are in normal mental health status. Some factors that influenced mental health during the COVID-19 pandemic, including gender, history of illness, and age among nurses in the government hospital in Padang City.